Pertanggungjawaban Hukum Perdata Terhadap Kerugian Konsumen Akibat Penggunaan Artificial Intelligence dalam Perspektif Hukum Positif Indonesia - Nina Rahmadania Yoki; Dinda Dinanti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of Artificial Intelligence (AI) technology has brought significant changes to various sectors of society, including e-commerce, financial services, healthcare, and digital services. The use of AI offers various conveniences that improve the efficiency and quality of services. However, despite these benefits, AI also has the potential to cause harm to consumers, such as errors in system decision-making, personal data leaks, and system failures resulting in material and immaterial losses. Legal issues arise because Indonesia currently lacks specific regulations comprehensively governing liability for losses caused by AI. This study aims to analyze the forms of civil legal liability for consumer losses resulting from the use of Artificial Intelligence and examine the forms of legal protection available under Indonesian positive law. This study uses a normative legal research method with both statutory and conceptual approaches. The results indicate that AI cannot yet be categorized as a legal subject, so liability remains with those who develop, operate, or utilize the technology. The basis for this liability can be found in the provisions of the Civil Code and the Personal Data Protection Law.